2022
DOI: 10.1177/09540083221093759
|View full text |Cite
|
Sign up to set email alerts
|

New polyimide ionomers derived from 4,4-diamino-[1,1-biphenyl]-2,2-disulfonic acid for fuel cell applications

Abstract: The set of important properties of polymers necessary for their use as fuel cell membranes, such as film-forming properties, stability in acidic aqueous media, thermal stability, proton conductivity, is determined by their chemical structure, which provides not only basic and fragmentary mobility of the polymer chain but also complex supramolecular structural features (in particular, phase separation). The effect of the chemical structure of aromatic polyimide sulfonic acids, containing a fragment of 4,4′-diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Agarwal et al [ 25 ] noted that the introduction of radical scavenger additives, such as cerium, is a promising solution to the problem of membrane destruction. One of the directions for membrane stabilization is the creation of membranes based on more stable ionomers [ 26 , 27 , 28 ]. Kononova et al [ 27 ] showed the prospects of polyimidesulfonic acid BDSA-SPI-4 (H) as a proton-conducting membrane polymer for electrochemical devices with direct energy conversion; a maximum electrical power of ~170 mW/cm 2 was reported in fuel cell mode in an oxygen/hydrogen system at room temperature and atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Agarwal et al [ 25 ] noted that the introduction of radical scavenger additives, such as cerium, is a promising solution to the problem of membrane destruction. One of the directions for membrane stabilization is the creation of membranes based on more stable ionomers [ 26 , 27 , 28 ]. Kononova et al [ 27 ] showed the prospects of polyimidesulfonic acid BDSA-SPI-4 (H) as a proton-conducting membrane polymer for electrochemical devices with direct energy conversion; a maximum electrical power of ~170 mW/cm 2 was reported in fuel cell mode in an oxygen/hydrogen system at room temperature and atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%